Isolationsanthropologie in Marlen Haushofers „Die Wand”. - Isapchuk, Yulia (My University, 2022)
The novel „The Wall” („Die Wand”, 1963) by the Austrian writer Marlen Haushofer (1920- 1970) is analyzed from the perspectives of modern literary anthropology. Attention is focused on the poetics of everyday life and the ways of communication during total isolation.  M. Haushofer's novel is an original invariant of man's adaptation to the new reality during a catastrophe and/or in the post-apocalyptic world. The metaphor of the wall allows the author to mark the borderline between society and people, civilization and nature. Total isolation makes it possible to take a fresh look at the stereotyped relationships between people and animals, which are not opposed but radically revised from the standpoint of communication on an equal footing. The poetics of everyday life reveals concrete mechanisms and models of the adaptation of living beings to isolation from the perspective of literary anthropology.
Keywords: Marlen Haushofer, „The Wall”, Isolation, Literary Anthropology, Literary Animal Studies, Poetics of Everyday Life.